Mosby's dictionary of medicine, nursing [and] health professions (Elsevier Mosby, 2006)
This title includes everything you would expect from a world-class dictionary ...plus so much more! This bestselling, full-colour dictionary of medical, nursing, and health care terminology is renowned for both its clear, complete definitions and its incomparable colour illustrations. This title features: no confusing sub-entries; straightforward alphabetical organization that helps you find a definition on the first try; new coloured terms and convenient thumb indexing that make searching easier; British spellings of selected entries that help you recognize alternative spellings; UK appendices to help your professional development. It also features: more than 2300 vibrant colour photographs and drawings that illustrate all subject areas; large, clear type that is easy to read; helpful tables that provide essential information at a glance; color Atlas of Human Anatomy that contains dozens of clearly labelled drawings. This title includes: comprehensive, authoritative definitions - including major diseases, disorders, procedures, and drugs - that offer the most accurate, complete information available; updated, expanded drug entries that include information on specific drugs currently on the market; hundreds of lab test definitions that describe and explain key lab and diagnostic tests; new and updated entries for herbs and complementary/integrative therapies that keep pace with health care trends. This title also features a website that provides hundreds of web links to help you find authoritative information online, as well as content updates and other helpful resources. Trusted by more health professionals and students for years, now the 7th edition is even better than ever, includes 5000 new definitions! It also includes new CD-ROM with valuable tools such as: complete, fully functional medical spellchecker, medical terminology activities, audio pronunciations, English-Spanish phrase translations, and more. All nursing diagnosis entries reflect the 2005-2006 NANDA terminology and the newest information from NIC and NOC. It contains: new and updated appendicxes that cover JCAHO changes in documentation, functional health patterns, new nutritional standards, and much more; UK appendices that include the NMC code of professional conduct, PREP, website directory of information sources, health care organizations and voluntary groups, career development via your CV, personal development and structured networking, research, evidence-based practice and web sources; expanded definitions of over 70 key conditions now contain full, detailed nursing process information. \"Mosby\'s Illustrated Dictionary of Medicine, Nursing & Health Professions, 7th Edition\" is the reference of choice when you need quick, informative, practical, vividly illustrated definitions of relevant health care terminology.
Keywords: lékařství; ošetřovatelství; Nursing; Dictionaries, Medical as Topic; lékařské slovníky jako téma; Medicine